Lipase Activity of Endophytic Actinobacteria from Medicinal Plants - Yulin Lestari; Budi Wirawan; Sri Budiarti; Min Rahminiwati (HAYATI Journal of Biosciences, 2018)
Endophytic bacteria are known to reside within host plant tissue without giving a harmfull effect. The endophytes may play an important role, as they may produce similar bioactive compounds as produced by the host plant. Various medicinal plants have long been used to cure diseases. Traditionally, leaves extract of Guazuma ulmifolia, Psidium guajava, or the rhizome of Curcuma xanthorrhiza can be used to treat disease, e.g. hyperlipidemic. The mechanism can be through lipase activity, where the lipase catalyzes the hydrolysis of triacylglycerol to fatty acids and acylglycerol. The objective of this research was to assess potency of endophytic bacteria as anti-hyperlipidemic compounds producer through their lipase activity. Sixty nine endophytic bacteria which comprised of 22, 27 and 20 isolates were isolated from the leaves of G. ulmifolia, P. guajava, and the rhizome of C. xanthorrhiza, respectively. Eight out of the 69 isolates showed lipase activity, and the two selected isolates, i.e. DPG 3(2) and AJB 4(4) were considered as good lipase producers. The highest specific lipase activity of DPG 3(2) isolate was observed for 0.874 units per mg at 38 h, whereas AJB 4(4) isolates had the specific lipase activity at 1.139 units per mg after 72 h observation. These data indicate that the two selected isolates have the potency as antihyperlipidemic compounds producer through their lipase activity.